Optimization of process parameters of micro-EDD/EDM for magnesium alloy using Taguchi based GRA and TOPSIS method. (2022) - Meel, Ramesh; Singh, Vijender; Katyal, Puneet; Gupta, Munish
Abstract: Magnesium based alloys are biocompatible, biodegradable and osteoconductive metallic materials having similar mechanical properties to that of bone are indeed a potential candidate for new generation biodegradable materials. For better osteointegration and reducing the stress shielding between the bone and implant, the µ-drilled perforated implants are required. Therefore, an attempt has been made in the present research work to optimize the process parameters on Mg based alloys through micro electric discharge drilling (µ-EDD/EDM) and to get the best parameters from a range of input parameters in order to get the ideal responses. L16 orthogonal array has been used for parameters, i.e. peak current (Ip ), pulse on time(Ton ), pulse off time(Toff ) and work piece thickness(WT) in order to find drilling rate (DR) and electrode wear rate(EWR). Taguchi method has been used in combination with ANOVA in order to optimize the single process parameters and it has been applied to find out the most significant parameters at 95% confidence level. Taguchi based Grey Relational Analysis(GRA) and Technique of preference by similarity to ideal solution (TOPSIS) have been used to optimize the multi process parameters into single parameter and their enhancement in the results is 0.350739 through GRA and 0.371970 through TOPSIS.